Comprehensive Evidence of Capital Structure and Firm Performance in Indonesia - Octavio, Danes Quirira; Miftahuddin, Muhammad (Telaah Bisnis, 2025)
This article investigate the effect of debt on firm performance in Indonesia. Annual unbalanced panel data from non-financial firm that listed between the year of 2010 and 2018 are examined. Besides using proxy of debt ratios, we also categorized debt based on its maturity: short-term and long-term debt ratios. To provide robust results, various methods are used in this study. Our method is not only limited on static regression (ie: pooled ordinary least square, fixed effect, and, random effect), but also dynamic panel regression, such as generalized method of moment-first difference. In addition, nonlinear regression is also conducted to investigate whether the effect of debt on firm performance in Indonesia follows U inversed pattern. Our result shows that there is negative effect between all debt category and firm performance. This result may indicate the existence of debt mismanagement in Indonesia as this negative effect is not resulted from U-inversed pattern. In addition, we found that short-term debt has a significant role in reducing firm performance. In other words, firms’ monitoring of debt, especially in short-term debt, is substantial. We suggest that firms should consider increasing the proportion of long-term debt over short-term debt since long-term debt has no negative significant effect on the firm’s performance.